Machine Translation 10th China Workshop, CWMT 2014, Macau, China, November 4-6, 2014. Proceedings - Shi, Xiaodong; Chen, Yidong (Springer eBooks, 2014)
This book constitutes the refereed proceedings of the 10th China Workshop on Machine Translation, CWMT 2014, held in Macau, China, in November 2014. The 10 revised full English papers presented were carefully reviewed and selected from 15 submissions of English papers. The papers cover the following topics: machine translation; data selection; word segmentation; entity recognition; MT evaluation.